Antileukemic activity of sulfonamide conjugates of arabinosylcytosine - Novotny, L.; Phillips, O.A.; Rauko, P; Miadokova, E. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
Aim: Cytosine arabinoside is routinely used for treatment of leukemias and lymphomas. However, because of its extensive metabolic inactivation and limited activity in chemotherapy, new analogues of araC are being tested. The aim of this work was to synthetize two araC conjugates and evaluates their cytotoxic/antileukemic activity. Methods: Synthesis of araC-sulfonamide conjugates A and B was performed in anhydrous conditions using cyclostyling and 5’-chlorocyclocytidine as starting material. Elemental analysis and NMR, IR and UV spectrometry were used for structure confirmation. The synthesized araC conjugates were tested for their cytotoxicity in L1210 leukemia cells in vitro and for therapeutic activity and toxicity in vivo in leukemia L1210-bearing mice. Results: The cytotoxic activities of araC and two synthesized conjugates A and B were expressed as IC50 (µmol/l) and were compared respectively. The conjugate A is 303-times less active and the conjugate B is 757-times less active than araC. Consequently, the antileukemic activity and the acute toxicity of these compounds were examined in experiments involving leukemia L1210-bearing mice. Statistically significant therapeutic outcome was observed when the dosage of both araC conjugates was increased 10-times compared to araC. Next, the ration of cytotoxicity vs therapeutic activity for araC and both conjugates was performed. It was recorded that the ration between cytotoxicity and therapeutic activity for araC is 3333, for the conjugate A and B, the ration is significantly lower (110 and 44). This indicates that the inactivation of araC conjugate A is 30-times slower and the inactivation of conjugate B is 75-times slower as araC inactivation. Conclusions: The differences in cytotoxic and therapeutic activity registered in araC treatment and between two araC-analogues are most probably caused by slow liberation of araC from both conjugates. We are considered that prolonged araC liberation protected them from inactivation and extended the time period of therapeutic action both araC conjugates. The obtained results can serve as stimuli for further investigation of new araC-analogues. Цитозинарабинозид (araC) используют при терапии лейкемии и лимфомы, однако ввиду его активной метаболической инактивации и лимитированной активности создаются и испытываются новые аналоги araC. Цель работы — синтез двух конъ-
югатов araC и оценка их цитотоксической/противо-лейкемической активности. Методы: синтез сульфонамидных конъюгатов
araC A и B проводили в безводном режиме с использованием 5-хлорциклоцитидина в качестве исходного материала. Для
подтверждения структуры использовали элементный анализ, ЯМР, ИК и УФ спектрометрию. Синтезированные конъюгаты
araC испытывали на цитоксичность против клеток лейкемии линии L1210 in vitro, а также на наличие терапевтической
активности и токсичности in vivo на мышах с экспериментальной опухолью L1210. Результаты: цитоксическую активность
araC и конъюгатов A и B выражали как 50 (µМ/л). Конъюгат A оказался в 303 раза менее активным, а конъюгат В — в 757
раз менее активен, чем araC. Противоопухо левую активность и острую токсичность соединений исследовали в экспериментах
in vivo. Статистически значимые различия в терапевтической эффективности препаратов отмечали при условии, если
дозы конъюгатов были в 10 раз выше, чем таковые araC. Отмечено, что в то время как соотношение между цитоксичностью
и терапевтической активностью для araC было 3333, то для конъюгатов A и B эта величина была значительно ниже (110
и 44 соответственно), что указывает на то, что инактивация конъюгатов А и В araC происходит в 30 и 70 раз медленнее
соответственно, чем инактивация araC. Выводы: различия в цитоксической и терапевтической активности araC и атов
вероятнее всего определяются медленнымвысвобождением araC, а продолжительный процесс высвобождения araC защищает
активное вещество от инактивации и увеличивает продолжительность терапевтического действия конъюгатов.